The U.P. Institute of Library Science an introduction using the multimedia approach - Lim, Rothman T. (1999)
Two computer-based orientation programs using multimedia approach were created in order to disseminate information about the U.P. Institute of Library Science. The study made use of slide presentation using Microsoft PowerPoint 97 and creation of WebPage.